Antibacterial and antibiofilm activities of Trollius altaicus C. A. Mey. On Streptococcus mutans. (December 2020) - Yan, Li; Wu, Wenxia; Tian, Shuge
Abstract: Dental caries is a chronic bacterial infectious disease caused by multiple factors, with Streptococcus mutans ( S. mutans ) as the main cariogenic bacteria. Trollius altaicus C. A. Mey. (TA) is a common folk medicine in the Xinjiang area of China. In this study, we investigated the inhibitory effect of T. altaicus C. A. Mey. (TA) flower extracts on S. mutans . The inhibition zone, minimum inhibitory concentration (MIC) value and minimum bactericidal concentration (MBC) value were investigated to determine the antibacterial activity of the extracts. Biolfilm study was used to determine the antibiofilm activity of the extracts. Results showed that the water, ethanol, and n -butanol extracts of TA flower against S. mutans had MIC values of 10, 5, and 10 mg/mL, respectively, and MBC values of 20, 10, and 20 mg/mL, respectively. Crystal violet staining assay showed that the inhibition rates of the biofilm were 78.10% ± 1.14%, 81.12% ± 3.33%, and 80.54% ± 3.60% at MIC levels of the water, ethanol, and n- butanol extracts of TA flower, respectively. Observation of the biofilm by confocal laser scanning microscopy and quantification of the biofilm via flow cytometry showed that the TA flower extracts could damage the biofilm. The TA flower extracts significantly inhibited biofilm formation at MIC value (P < 0.05). These results showed that the water, ethanol, and n -butanol extracts of TA flower had inhibitory effects on the planktonic growth and biofilm formation of S. mutans . The ethanol extract had the strongest inhibitory effect among the three extracts. Therefore, TA flower has bacteriostatic activity against S. mutans and has the potential to be developed for the prevention of dental caries. Graphical abstract: Image 1 Highlights: The water, ethanol, and n -butanol extracts of Trollius altaicus C. A. Mey. flower effectively inhibited the planktonic growth and biofilm formation of Streptococcus mutans. The ethanol extract of T. altaicus C. A. Mey. flower had the strongest inhibitory effect on the planktonic growth and biofilm formation of Streptococcus mutans. T . altaicus C. A. Mey. flower has potential applications in the prevention of dental caries.